Detection of Israel variant 2 (IS/1494/06) genotype of Infectious Bronchitis Virus in a layer chicken flock - Ongor, Hasan; Timurkaan, Necati; Coven, Fethiye; Karabulut, Burak; Eroksuz, Hatice; Cetinkaya, Burhan; Carli, Kamil Tayfun (Ankara Univ Press, 2021)
The aim of this study was to determine an infectious bronchitis (IB) infection, caused by an Israel variant 2 (IS/1494/06)-like IBV, in a layer chicken flock regularly vaccinated with vaccines containing IBV H120 and 4/91 strains. Mild respiratory symptoms, drop in egg production and soft-shelled eggs and eventually death were observed in a layer chicken flock. Clinical samples from four diseased chickens were examined for the detection and genotyping of IBV by virus isolation, a commercial real time reverse transcription polymerase chain reaction (rRT-PCR) and nucleotide sequencing. Both Israel variant 2 (IS-Var2) and 793/B serotypes were detected from samples by rRT-PCR, but sequencing results of a 345 bp part of S1 gene revealed that our IBV isolate, HFT-IBV, was IS/1494/06 (IS-Var2)-like with the 97.7% genetic similarity. These results suggested that immunity against vaccination with a combination of different genotypes (H120 and 4/91) could not be protective for IS-Var2 IBV field infection. In addition, identification of genotypes from the clinical samples, such as swabs and organ samples by commercial rRT-PCR assays failed to find correct IBV genotype responsible for the IB infection, whereas analysis of nucleotide sequencing of S1 gene of IBV as a gold standard test undoubtedly detected causative genotype of the infection. Also, the findings indicated that there is an urgent need for consider genotype- or protectotype-match vaccination strategies in the field to prevent vaccine- and IB-dependent economic losses of the poultry sector and logically protect chickens from IBV infection.
Yumurtacı bir tavuk sürüsünde ınfeksiyöz bronşit virüsünün İsrail varyant 2 (IS/1494/06) genotipinin tespiti
Keywords: Genotype; Infectious Bronchitis Virus; Israel variant 2; Layer chicken; vaccination